The Role of BK Teachers in Shaping Students' Personality to Become Superior Persons for Class XI Science SMAN 1 Koto XI Tarusan - Adison, Joni; S, Suryadi (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2022)
This research is motivated by the existence of guidance and counseling teachers who have not been able to shape the students' personalities to become better individuals. The purpose of this study was to determine 1) the role of guidance and counseling teachers in shaping the noble character of students. 2) The role of guidance and counseling teachers in shaping the independence of students. 3) The role of guidance and counseling teachers in shaping student discipline. 4) The role of guidance and counseling teachers in shaping students' selfconfidence. This study uses research methods using a descriptive approach. The subjects in this study were guidance and counseling teachers as well as students and peers. Data collection was taken through interviews and observations. The researcher acts as a direct interviewer to collect data through guidance and counseling teachers as well as students and peers. The results of the study are: 1) The role of guidance and counseling teachers in shaping the noble character of students is in the good category. 2) The role of guidance and counseling teachers in shaping the independence of students is in the good category. 3) The role of guidance and counseling teachers in shaping student discipline is categorized as good. 4) The role of guidance and counseling teachers in forming students' self-confidence is in the good category. This research is recommended to guidance and counseling teachers in order to improve student behavior to become better individuals